Students’ Online Experiences in Online Collaborative Writing with Focus on Language Rules - Herlinawati, Herlinawati; Isnawati , Uzlifatul Masruroh; Yudar, Ratih Saltri; Syahdan, Syahdan; Syaifullah, Syaifullah (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Collaborative works among pairs, groups or one pair with another pair are favoured to accomplish, particularly in writing tasks. Students cannot undertake collaborative revision face-to-face during classroom instruction in EFL writing during the pandemic. Therefore, online collaborative revision has become a practical solution, especially in the context of EFL writing classes. This study aims to apprehend students' experience in online collaborative writing revision in the L2 writing context, focusing on language rules. This study employed qualitative research with a narrative inquiry as a research design. A proportionate interview with probability sampling is used as the main instrument to collect data from the EFL students at the Department of Teacher Training and Education, Universitas Lancang Kuning. Five students from the seventh semester who had taken an argumentative writing class were chosen as the participant. The findings reveals, through experiencing online collaborative writing revision, students were knowledgeable and well-improved in revising their writings, particularly on language rules. The analysis showed the students managed to share multiple perspectives on how they are experiencing the online collaborative writing revision. In conclusion, online collaborative writing revision helps students with their writing revision through the feedback they obtain during the activities in the class and makes them have an exceeding writing performance. The expected contribution from this research is to gain an exceeding description of students' needs in implementing online collaborative writing revision.